![image](https://tex.z-dn.net/?f=lim_%7Bx-%3E%5Cinfty%7D+%281-%5Cfrac%7B9%7D%7Bx%7D%29%5Ex%3D%5C%5C%5C%5Clim_%7Bx-%3E%5Cinfty%7D+%281%2B%5Cfrac%7B1%7D%7B%5Cfrac%7B-x%7D%7B9%7D%7D%29%5E%7B%5Cfrac%7B-x%7D%7B9%7D%2A%28-9%29%7D%3De%5E%7B-9%7D)
\infty} (1-\frac{9}{x})^x=\\\\lim_{x->\infty} (1+\frac{1}{\frac{-x}{9}})^{\frac{-x}{9}*(-9)}=e^{-9}" alt="lim_{x->\infty} (1-\frac{9}{x})^x=\\\\lim_{x->\infty} (1+\frac{1}{\frac{-x}{9}})^{\frac{-x}{9}*(-9)}=e^{-9}" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=lim_%7Bx-%3E3%7D+%28x%5E3%2B2x%5E2-5x%2B1%29%3D3%5E3%2B2%2A3%5E2-5%2A3%2B1%3D31)
3} (x^3+2x^2-5x+1)=3^3+2*3^2-5*3+1=31" alt="lim_{x->3} (x^3+2x^2-5x+1)=3^3+2*3^2-5*3+1=31" align="absmiddle" class="latex-formula">